Hand-Assisted Laparoscopic Surgery Is Superior to Open Liver Resection for Colorectal Liver Metastases in the Posterosuperior Segments - Abu-Zaydeh, Omar; Sawaied, Muneer; Berger, Yael; Mahamid, Ahmad; Goldberg, Natalia; Sadot, Eran; Haddad, Riad (Frontiers in Surgery, 2021)
Introduction Laparoscopic liver resections (LLR) of colorectal metastasis located in posterosuperior segments (1, 4A, 7 and 8) are challenging and highly demanding. The aim of our study is to determine the safety and feasibility of hand-assisted laparoscopic surgery (HALS) in the resections of the posterosuperior lesions and to compare the peri-operative, short-term and long-term outcomes with the open liver resection (OLR) approach. Methods and results A retrospective study of patients who underwent either HALS or OLR for metastatic colorectal cancer (mCRC) located in the posterosuperior segments of the liver between 2008 and 2018 in two university affiliated medical centers. Results A total of 187 patients were identified, of whom 78 underwent HALS and 109 underwent OLR. There was no difference between the HALS and OLR with regard to preoperative factors (age, primary CRC tumor location, number and anatomical distribution of liver metastasis, pre-operative neo-adjuvant treatment, operative time, blood transfusion rate, and resection margins positivity). On the other hand, HALS compared to OLR had a significantly shorter mean hospital stay (4 versus 6 days; P=.003), and a lower total complications rate (25% versus 47% P=.006). Both groups had no 30-day mortality. Also, patients who underwent HALS versus OLR had similar liver metastases recurrence (55% versus 51%. P= 0.65) and 5-year survival (47% versus 45%. P= 0.72). Conclusions HALS for mCRC located in posterosuperior liver segments is safe and feasible and it is a preferable approach due to its lower complication rate and shorter hospital stay while not compromising survival and disease recurrence.